Structured image diagnosis of vertebral body degeneration and disc damage - Binary image criteria and comparison for systematic image analysis in occupational diseases 2108/2110 - Braunschweig, Rainer; Kildal, Daniela; Meyer-Clement, Michael; Janka, Rolf; Tiemann, Andreas (RöFo : Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebende Verfahren, 2024)
Occupationally related limitations of earning capacity can be recognized under social legislation and may be subject to compensation ("reduction in earning capacity"). For this purpose, legislators have defined a list of occupational diseases ("BK list"). Recognition of an occupational disease requires a legal assessment procedure based on a medical appraisal. The aim of the assessment is to prove the "causality" and the "causality giving rise to liability". In addition to clinical findings and workplace analyses, imaging methods (projection radiography, MRI) are primarily used to substantiate liability. These methods enable proof of load-conforming damage patterns for occupational diseases 2108/2110 (damage to intervertebral discs). In addition to the legal background, the following review article primarily presents the image criteria for load-conforming damage patterns of the spine. On the basis of the consensus paper on the "Assessment of occupational disc diseases of the lumbar spine", image criteria are assigned to age-atypical grades of findings, and "typical constellations of findings" are defined for vibration (BK 2108) or lifting (BK 2110) loads. The aim of Part 1 is to explain the image criteria of the comparative images presented as image plates in Part 2 and thus to present a reference catalog of findings. · Occupational diseases are defined by legislators in the "List of Occupational Diseases".. · For occupational intervertebral disc diseases (BK 2108/2110), constellations of findings are defined.. · In the context of imaging diagnostics, a large number of image criteria are used.. · Part 1 explains the basics.. · Part 2 provides the image criteria on the basis of "comparative images" as a reference catalog.. · Braunschweig R, Kildal D, Meyer-Clement M et al. Structured image diagnosis of vertebral body degeneration and disc damage - Binary image criteria and comparison for systematic image analysis in occupational diseases 2108/2110. Fortschr Röntgenstr 2024; 196: 347 - 353.